Positivism and Metaphysics - Laskienė, Skaistė (Problemos, 1995)
The problem of the demarcation of metaphysics and science in positivism is discussed. It is shown that for the first time the problem was put forward by D. Hume. The evolution of the problem in positivism is described. Finally, the conclusion is drawn, that the problem cannot be solved relying on the logical criteria only.